Preoperative serum thymidine kinase activity as novel monitoring, prognostic, and predictive biomarker in pancreatic cancer - Felix, Klaus M.; Hinz, Ulf; Dobiasch, Sophie; Hackert, Thilo; Bergmann, Frank; Neumüller, Magnus; Gronowitz, Simon; Bergqvist, Mattias; Strobel, Oliver (Pancreas, 2018)
Objective: The aim of the study was to investigate serum thymidine kinase 1 (S-TK) activity as a diagnostic and prognostic marker for patients with pancreatic ductal adenocarcinoma (PDAC). Methods: Using the sensitive TK activity assay DiviTum, preoperative serum samples from 404 PDAC, 28 chronic pancreatitis, and 25 autoimmune pancreatitis patients and 83 healthy volunteers were analyzed. The preoperative S-TK activities of 54 PDAC patients who received neoadjuvant therapy (nTx) were also compared with those of 258 PDAC patients who did not receive nTx. Results: The preoperative S-TK activities of PDAC patients were significantly higher and discriminatory from autoimmune and chronic pancreatitis patients and control groups. The S-TK activity in PDAC patients was associated with overall survival. Patients with S-TK activity of less than 80 Du (DiviTum units)/L demonstrated median survival of 20.3 months with an estimated 18.0% 5-year survival rate; for S-TK activity of 80 Du/L or greater, median survival was 15.1 months with a 6.8% 5-year survival rate. For early-stage PDAC, these differences were even more pronounced. The S-TK activity in the nTx group was significantly higher than that in the group not receiving nTx. Conclusions: Pancreatic ductal adenocarcinomas reveal a significant increase in S-TK activity, which is associated with overall survival, especially in early tumor stages. Serum thymidine kinase 1 activity may be a useful parameter for monitoring nTx efficacy.